109k views
4 votes
If f(x) = 4-x* and g(x) = 6x, which expression is equivalent to (g -)(3)?

O 6-3- (4 + 3)²
O6-3- (4- 3)
O 6(3) -4 +32
O 6(3) –4 -32

If f(x) = 4-x* and g(x) = 6x, which expression is equivalent to (g -)(3)? O 6-3- (4 + 3)² O-example-1

1 Answer

4 votes

Answer:

The expression that equivalent to (g - f)(3) is 6(3) - 4 + 3² C

Explanation:

Let us solve the question

f(x) = 4 - x²

g(x) = 6x

→ Find at first (g - f)(x) by subtracting f(x) from g(x)

∵ (g - f)(x) = 6x - (4 - x²)

→ Remember (-)(+) = (-) and (-)(-) = (+)

∴ (g - f)(x) = 6x - 4 + x²

→ Substitute x by 3 to find (g - f)(3)

∵ (g - f)(3) = 6(3) - 4 + (3)²

(g - f)(3) = 6(3) - 4 + 3²

The expression that equivalent to (g - f)(3) is 6(3) - 4 + 3²

User Conny Olsson
by
5.9k points